2007
DOI: 10.1002/chem.200700558
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Grignard Reagents: Challenges and Possibilities of Aryl Alkaline Earth Metal Compounds

Abstract: Compounds of the type aryl--M--X, with M=Ca, Sr, Ba and X as any kind of ligand (such as halide, phosphanide, amide, aryl), are presented. The low reactivity of the heavy alkaline earth metals calcium, strontium, and barium enforces an activation prior to use for the direct synthesis. The insertion of these metals into C--I bonds of aryl iodides (direct synthesis) yields aryl metal iodides and has to be performed at low temperatures and in THF. Aryl alkaline-earth-metal compounds show some characteristics: 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
75
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(85 citation statements)
references
References 131 publications
5
75
0
5
Order By: Relevance
“…The chemistry is simplified by the absence of Ca 2 + redox chemistry. [19][20][21][22][23][24] Treatmento fy tterbium with iodobenzene in thf yields ar ed solution described as "PhYbI"(thf) x . [25] Although written as containing divalent ytterbium, the mixture contains trivalents pecies, as proposedb yE vanse tal.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry is simplified by the absence of Ca 2 + redox chemistry. [19][20][21][22][23][24] Treatmento fy tterbium with iodobenzene in thf yields ar ed solution described as "PhYbI"(thf) x . [25] Although written as containing divalent ytterbium, the mixture contains trivalents pecies, as proposedb yE vanse tal.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, the understanding of the coordination chemistry of the elements of the heavy alkaline earth metals (M = Ca, Sr, Ba) has advanced dramatically, owing primarily to an interest in their application as chemical vapour deposition precursors (Hanusa 1990(Hanusa , 1993(Hanusa , 2000(Hanusa , 2002Westerhausen 1998Westerhausen , 2001Westerhausen , 2006Westerhausen , 2008Alexander & Ruhlandt-Senge 2002;Westerhausen et al 2007). Reaction studies upon organometallic compounds of calcium, strontium and barium have, however, been largely overshadowed by those of the lighter congener, magnesium.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable skill was required to isolate the compounds at low temperatures and to obtain crystals for X-ray studies. [13] The greater stability of 2,4,6-triphenylphenyl derivatives, however, suggested that the nucleophilicity of the carbanion could be sufficiently reduced by delocalization to prevent attack on the solvent. The reaction of 1-bromo-2,4,6-triphenylbenzene with activated magnesium in the traditional way yielded the Grignard reagent 5 (Scheme 3) as colorless needles.…”
Section: Theorganometallicchemistryofthes-blockelements-frommentioning
confidence: 98%
“…[13,14] The Ca I derivative 6, which contains no CaÀCa bonds, represents a further important step in the study of this unusual oxidation state.…”
Section: Theorganometallicchemistryofthes-blockelements-frommentioning
confidence: 99%